Red color characterization in several Roman frescos and paintings by in situ and remote LIBS, LIF and Raman Spectroscopies - Roberta Fantoni; Violeta Lazic; Francesco Colao; Salvatore Almaviva; Adriana Puiu (Ge-conservación, 2022)
Nowadays, in situ pigments characterization on a cultural heritage relevant surface is possible by using combined laser spectroscopies which are suitable to detect at high resolution both molecular (Raman, LIF) and atomic sample composition (LIBS), the latter with stratigraphic capabilities and high sensitivity for trace detection. Their applications are here reported regarding the identification of historical pigments and dyes on different substrates, particularly in wall paintings, from pre-historic times up to the XIXth century when the use of synthetic substances became common. In this paper attention is focused on red colors, known since antiquity for the additional ritual and medical use. Their pictorial use along the centuries is shown and in selected cases provenances hypothesis, based on historical information, could be supported by results of composition analysis and elemental trace detection made possible by the application of laser technologies.